HISTOLOGICAL FEATURES OF VASCULAR COMPLICATIONS OF THE LOWER EXTREMITIES IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Volos, Liliya; Mykhaylichenko2 , Tetyana (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES The aim of the work was to investigate histological features of vascular complications of the lower extremity in patients with type 2 diabetes mellitus. METHODOLOGY We studied macroscopic and microscopic changes of lower extremitytissues of 7 cases of diabetic gangrene. We used common histological methods of staining with hematoxylin and eosin, Masson’s trichrome and Hart’s elastin stain. RESULTS The main histological features of the vascular complications of lower extremity in patients with type 2 diabetes mellitus were: atherosclerosis arteries and thrombus formation; calcification of the middle tunica of arteria, including large areas of calcification and many small areas and proliferation of endothelium; thinning of the epidermis; thickening and fragmentation of fibrous structures in the dermis; reduction in skin appendage; hyalinosis and vascular thrombosis. In diabetic gangrene, skin defects of various depths and areas are determined with microcirculatory disorders, stasis, thrombus formation, wall hyalinosis, accumulation of purulent exudate and tissue detritus in the interstitial tissue. Pathomorphological criteria for the viability of the lower extremity tissues in diabetic foot and gangrene are the patency of large vessels, the integrity and clear differentiation of tissue structures, the arterioles wall thickness in the range 18.5 ± 1.5 μm, the diameter – 29.7 ± 0.8 μm, Kernogan index – 0.67 ± 0.08. CONCLUSION The main cause of disability and mortality in patients with diabetes mellitus is late vascular complications, including diabetic micro- and macroangiopathy of the lower extremities. Timely diagnosis of and adequate treatment can prevent the development of diabetic foot syndrome.